Research on Equity, Poverty and Health Outcomes : Lessons for the Developing World - Wagstaff, Adam (World Bank, Washington, DC, 2013)
This paper provides a selective survey of the literature to date on poverty, equity and health outcomes. It begins with an overview of the methods that can be used to measure poor/non-poor inequalities in health outcomes, and then reviews the evidence on the extent of these inequalities in low and middle-income countries (LMICs). The data presented relate mostly to children, but some results are also presented on adults. The paper then presents a conceptual framework for understanding the causes of poor/non-poor inequalities in health outcomes, distinguishing between the effects of inequalities in the proximate determinants of health, and inequalities in the socioeconomic or underlying determinants. The paper goes on to review the evidence on what these determinants are, and how far inequalities in them appear to explain inequalities in health outcomes. The final part of the paper examines the influence of policies and programs on inequalities in health outcomes, reviewing both studies that shed light on the effects of broad policies.